Effect of Aerobic Exercises on Plasma Adiponectin Level in Type 2 Diabetic Patients - KHASHABA, Ahmed (International Journal of Innovative Research in Medical Science, 2018)
Objective: To examine the effect of aerobic exercises on plasma adiponectin and HbA1c levels in type 2 diabetic patients. Material and methods: 136 patients with type 2 diabetes (age between 22 and 77 years) recruited from the outpatient clinics, Kasr Alaini, Egypt were randomly allocated into two groups. Group A (n=63) was the control group which followed only medication and diet program while group B (n=73) was the study group which followed the medication, diet program and performed aerobic treadmill exercise at moderate (50-80% of VO2max by 50% of maximum heart) three times per week for six weeks. Blood samples of plasma adiponectin were taken and recorded before and after the completion of the exercise program. Results: Adiponectin levels were elevated following the exercise program of moderate intensity (study 5.84±.09 versus control 5 ±.2 ug/mL). In comparison to baseline, adiponectin levels (study 4.12 ±.22versus control 4.07± .183 ug/mL) . Conclusion: Moderate intensity aerobic exercise result in a significant increase in plasma adiponectin levels in type 2 diabetic patients